2018
DOI: 10.1002/admi.201801016
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylaluminum Diffusion in PMMA Thin Films during Sequential Infiltration Synthesis: In Situ Dynamic Spectroscopic Ellipsometric Investigation

Abstract: Sequential infiltration synthesis (SIS) provides a successful route to grow inorganic materials into polymeric films by penetrating of gaseous precursors into the polymer, both in order to enhance the functional properties of the polymer creating an organic-inorganic hybrid material, and to fabricate inorganic nanostructures when infiltrating in patterned polymer films or in selfassembled block copolymers. A SIS process consists in a controlled sequence of metal organic precursor and co-reactant vapor exposure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
70
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(100 citation statements)
references
References 51 publications
(67 reference statements)
9
70
1
Order By: Relevance
“…These data indicate that, in the presence of MMA units in the polymer matrix, the amount of Al 2 O 3 grown during the SIS process is directly proportional to the concentration of MMA units in the RCP chains. This picture is perfectly consistent with previous experimental results showing that CO functional groups in the MMA units act as seeds for the growth of Al 2 O 3 during the SIS process …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These data indicate that, in the presence of MMA units in the polymer matrix, the amount of Al 2 O 3 grown during the SIS process is directly proportional to the concentration of MMA units in the RCP chains. This picture is perfectly consistent with previous experimental results showing that CO functional groups in the MMA units act as seeds for the growth of Al 2 O 3 during the SIS process …”
Section: Discussionsupporting
confidence: 93%
“…By means of in situ SE analysis, it is possible to measure thickness variation of the polymeric film during the SIS process in real time and to obtain information about TMA diffusion kinetics during the infiltration process . Analysis of ex situ data indicates that the amount of Al 2 O 3 that is grown per unit volume in a P(S‐ r ‐MMA) matrix is independent of the thickness of the polymer film for each specific MMA fraction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the ALD process, the subsequent exposure of the surface to precursors, separated by purging agents leads to cyclic surface modifications, and the control of which may play a critical role in the resulting thin film quality. To the best of our knowledge, unraveling such complex processes have not been attempted previously by in-situ spectroscopic ellipsometry in ALD or PEALD growth of ultra-thin films 41,46,[64][65][66][67][68][69][70][71][72][73][74][75][76][77] . The analysis of the evolution of the optical properties of ultra-thin films during growth cycles in ALD using in-situ SE as reported here in our work using the dynamic dual box model may gain further insight into the kinetics of the surface modifications within individual cycles.…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ Klaus et al suggested the application of in-situ SE during ALD growth processes 64 , and accurate thickness monitoring was reported for metal nitride thin films 41,65,66 and metal oxide thin films 46,[67][68][69][70][71][72][73][74][75][76][77] , for example. In these previous reports, in-situ SE data was measured once for every ALD cycle in order to determine the thickness GPC.…”
mentioning
confidence: 99%